THE LONG - TERM UNEMPLOYMENT AND POVERTY AS AN INTERDISCIPLINARY PROBLEM - Miriam Hlinkova (European Scientific Journal, ESJ, 2013)
The author in her article focuses on the issue of long-term unemployment and poverty, which often results in interdisciplinary problems. It is a problem of the whole society, which needs to be constantly looked into and it also constantly needs the elimination of the outside world´s effects on it. The aim of this work is to highlight the seriousness of this problem, the need for its elimination, with emphasis on the confrontation between scientific disciplines and their connections.